Regionai disparities and spatial spillovers: the impact of fintech on manufacturing productivity in China - Wang, Di; Tang, Xiao; He, Bin (Transformations In Business & Economics, 2026)
As China’s financial industry enters a new digital era, the scope of financial technology services to the real economy has expanded and deepened. This paper adopts spatial econometrics to examine the impact of FinTech on manufacturing productivity, specifically on manufacturing technology progress and efficiency improvement. The following conclusions are drawn. First, FinTech development tevels in China vary, with the highest level in the east, followed by the centrai region, and is the lowest in western China. Second, China’s fotai factor productivity presents clear spatial autocorrelation characteristics. Third, the development of FinTech can improve the manufacturing fotai factor productivity nationwide, and this effect occurs mainly through efficiency improvements, and the influence of technological progress is not significant. This study helps elucidate the possible spatial correlation effects of FinTech on manufacturing fotai factor productivity in terms of geographic location or socioeconomic factors. We also provide a reference for national policy deparlments to formulate differentiated interregional FinTech strategies.